2005
DOI: 10.5254/1.3547881
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc Complexes as Activator for Sulfur Vulcanization in Various Rubbers

Abstract: Because of environmental concerns, the zinc content in rubber compounds has come under scrutiny; therefore it is necessary to explore possibilities to reduce this zinc content. In this article the application of several zinc complexes as activator for sulfur vulcanization are discussed, in order to find alternatives for the conventionally used ZnO and fatty acid activator system. The effects of different zinc complexes on the cure and physical properties of two widely different rubbers, viz. EPDM and s-SBR, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 0 publications
4
74
0
Order By: Relevance
“…According to Heideman et al [7] different reactivities of zinc complexes result from their different basicity. The alkaline character of activator accelerates the sulphur vulcanization of rubber.…”
Section: Effect Of Zinc Complexes On Vulcanizationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Heideman et al [7] different reactivities of zinc complexes result from their different basicity. The alkaline character of activator accelerates the sulphur vulcanization of rubber.…”
Section: Effect Of Zinc Complexes On Vulcanizationmentioning
confidence: 99%
“…Complexes of Zn 2+ ions with accelerators are believed to be more reactive than the free accelerator and allow sulphur insertion to occur more rapidly [6]. Next, the complexes interact with sulphur or sulphur donors, generating the active sulphurating agent, which reacts with allylic sites of rubber chains to form crosslink precursors [7]. Forming these rubber bound intermediates is a key stage in accelerated sulphur vulcanization.…”
Section: Introductionmentioning
confidence: 99%
“…Das et al [10] developed a rubber composite based on zinc-stearate-modified LDH with NBR that does not require the incorporation of ZnO and stearic acid in the sulfuric curing system. In our work, the advantage of using unmodified magnesium/aluminum LDH in elastomer systems (XNBR or its hydrogenated counterpart HXNBR) lays in the possibility of full replacement of conventional metal oxide curatives used for functionalized elastomers (XNBR, HXNBR), particularly ZnO, which is believed to be harmful for the environment [22]. While crosslinking XNBR with a conventional sulfur vulcanizing system or ZnO is well known and commonly used, the application of magnesium aluminum layered double hydroxides MgAl-LDH for crosslinking process of XNBR is still a relatively new approach.…”
mentioning
confidence: 99%
“…In conjunction with that, it was also noticed that the cure time (t 90 ) of the NR compounds in the presence of the MgO were found to some extent lower than the NR compound with ZnO utilization. It was reported that MgO possess slightly slow rate of cure during vulcanization reaction [2][3][4][5][6], hence lower t 90 values achieved for NR compounds with MgO loadings were much expected. Meanwhile, the MH, which can be regarded as a measure of modulus were found increased with increased of the MgO loadings and similar trend was observed on the ML values, which represent the rubber compounds' viscosity behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, zinc oxide (ZnO) was used to catalyze rubber vulcanization process. Its mechanism during vulcanization process [4,8,9,12] and its effects on the properties of the vulcanizates [3][4][5][6][7]9,11] has long been known and investigated. However, ZnO release into the environment that occurs during production, disposal and recycling of rubber products, which is in soluble zinc compounds is classified as ecotoxic to aquatic organisms [5,7,[9][10].…”
Section: Introductionmentioning
confidence: 99%